Actuation system design for solar car - Syed Mohamad Amiruddin, Syed Saleh (2010)
This report is an explanation about actuation system design for solar car. The word actuation is almost same with propulsion. This actuation system involved motor, motor controller and transmission system. Actuation system is vital in order to make sure solar car able to run smoothly when power is supplied. Without proper actuation system design, the power system design that been developed by other person is useless. This system also crucial to ensure safety to driver when driving solar car. Analyses have been done to select suitable electrical device before the devices have been bought. Besides, in this report, motor mounting bracket have been designed and analyzed in software ALGOR. The purpose is to ensure the bracket can withstand vibration of motor and avoid failure. Comparison between AC motor and DC motor are made to compare the torque and power produced. Solar car use simple transmission which is belt drive. Gear ratio analysis is made to ensure correct ratio and car can move with no problem. Then gear ratio analysis is used to consider which torque converter is suitable. This project is successfully completed when every basic part needed for actuation system is analyzed and designed.